Analisis Perbedaan Kemampuan Interpretasi Data Numerasi Mahasiswa Pendidikan Biologi di Kalimantan Selatan Berdasarkan Masa Studi yang Telah Ditempuh - Arsyad, M. (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
Numeracy literacy is important for biology education students as pre-service teachers. Numeracy literacy ability can support students in conducting analyses related to quantitative data. Meanwhile, for biology teachers, numeracy literacy ability can support the process of analysis and evaluation of learning that is closely related to quantitative data. One indicator of numeracy literacy is the ability to interpret numerical data, which can support 21st-century learning competencies. This study aims to analyze differences in the ability to interpret numerical data for biology education students in South Kalimantan based on the study period that has been taken. This type of research is quantitative comparative research. The sample subjects for this study were 245 students of the Biology Education study program in South Kalimantan. The instrument for measuring the ability to interpret numeracy data was collected using a test instrument referring to AACU (2009). Data were analyzed using the ANOVA test and continued with Duncan's test to analyze differences between groups of students based on the study period that has been taken. The results showed significant differences in the ability to interpret numerical data for biology education students based on the study period that has been taken.